Pengaruh Profitabilitas, Risiko Kredit, Dewan Komisaris Independen Terhadap Kepercayaan Investor dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Bank yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020-2023 - Asyifa, Nita Laila (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the effect of profitability, credit risk, and independent board of commissioners on investor confidence, with firm size as a moderating variable, in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The research method used is quantitative, with secondary data sources. The results show that profitability and independent board of commissioners have a significant positive effect on investor confidence, while credit risk does not have a significant effect. Firm size strengthens the influence of profitability on investor confidence but does not moderate the effect of credit risk and independent board of commissioners. Simultaneously, profitability, credit risk, and independent board of commissioners affect investor confidence.